2011
DOI: 10.1111/j.1526-4610.2011.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue Therapy for Acute Migraine, Part 1: Triptans, Dihydroergotamine, and Magnesium

Abstract: Although there are relatively few studies involving health-care provider-administered triptans or DHE for acute rescue, they appear to be equivalent to the dopamine antagonists for migraine pain relief. The relatively rare inclusion of a placebo arm and the frequent use of combination medications in active treatment arms complicate the comparison of single agents with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 61 publications
(62 reference statements)
0
40
0
2
Order By: Relevance
“…As with adults who utilize the ER for their headache exacerbations, pediatric headache experts have shied away from the prescribing of narcotics . Judicial use of Intravenous fluids, NSAIDs, dopaminergic agents, magnesium, valproate, and Dihydroergotamine (DHE) have been used successfully 24,65,79‐83. Steroids are used as anti‐inflammatory agents, and their roles in the ER settting have been summarized well for adults …”
Section: Er and Inpatient Managementmentioning
confidence: 99%
“…As with adults who utilize the ER for their headache exacerbations, pediatric headache experts have shied away from the prescribing of narcotics . Judicial use of Intravenous fluids, NSAIDs, dopaminergic agents, magnesium, valproate, and Dihydroergotamine (DHE) have been used successfully 24,65,79‐83. Steroids are used as anti‐inflammatory agents, and their roles in the ER settting have been summarized well for adults …”
Section: Er and Inpatient Managementmentioning
confidence: 99%
“…Although adult headache studies report the common side effects with i.v. magnesium, including flushing from 8% to almost all patients in another cohort, lightheadedness, and burning at the site of infusion in up to 25%, these were not as common in our sample of adolescents and could be partly attributed by our slow infusion rate (6). …”
Section: Discussionmentioning
confidence: 63%
“…Some studies have shown i.v. magnesium to be effective for migraines and associated features, and others have shown no improvement compared with placebo (5,6,9,10). To our knowledge, there are no controlled studies in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they have had a myocardial infarction and an ulcer so both triptans and NSAIDs are contraindicated, over‐the‐counter medications do not work, and they do not want to take or the providers do not want to give opioids. Third, most headache specialists do not report prescribing rescue medication, a major potential strategy for preventing ED visits . These medications can be given if the typical migraine acute medication does not work; migraine rescue medications provide relief at home, so the patient does not have to go to the emergency room.…”
Section: Discussionmentioning
confidence: 99%